Computational Fluid Dynamics: Flow Analysis on the Effect of Different Jet Orifice Angle Multi Circular Jet for Fuel and Air Mixing - Kamaruddin, Ridzwan; Sulaiman, Syabillah; Khalid, Amir; Arafat, Mohammad; Jaat, Norrizam; Zainal Abidin, Shaiful Fadzil; Mohamed, Norirda; Yasak, Mohd Fuad (semarak ilmu, 2024)
affecting the combustion performance and emissions of the internal mixing air-assisted atomizers. Air-assisted atomizers are introduced to counter the low-pressure differential of a simplex nozzle, which reduces the atomization quality. The present study aims to determine the effects of Multi Circular Jet (MCJ) plates on the geometrical configurations of internal flows in mixing chamber and the internal flow of plate 3 using different properties of fuel. In this study, the realizable k-ε turbulence model, specifically designed for strongly swirling flows, is validated through numerical simulations. The turbulence model selected is a type of Reynolds averaged NavierStokes (RANS) model called the k-ε model. The MCJ plates provide the primary air entrance into the mixing chamber. Additionally, it acts as a turbulence generator and can be adjusted to alter the flow of fuel and air mixtures in a mixing chamber. The study compares several MCJ geometries in terms of pressure, speed, turbulent kinetic energy, and volume fraction and compares the performances of diesel and Crude Palm Oil (CPO) B30 biodiesel fuels. The findings imply that CPO B30 biodiesel has superior atomization and mixing due to its higher density and turbulent kinetic energy. CPO B30 biodiesel was compared to Diesel in terms of maximum pressure, average speed, turbulent kinetic energy per unit mass, and volume fraction. The results indicate that CPO B30 has lower pressure and higher velocity than Diesel, suggesting better fuel atomization and mixing. The higher density of CPO B30 leads to increased turbulent kinetic energy, improving fuel-air mixing inside the combustion chamber. The study demonstrates that the use of MCJ plates can enhance mixing in a mixing chamber. In addition, MCJ plates show the ability to control the spray and atomization. The findings of this study contribute to a better understanding of the relationships between geometry and fuel-air mixing, as well as the characteristics of the internal mixing airassisted atomizer, which will lead to future burner system improvements.